Assessment of the epilepsy treatment gap in two cities of south-east of Brazil A lacuna de tratamento em epilepsia em duas cidades do sudeste do Brasil - Ana Lúcia Andrade Noronha; Lúcia Helena Marques; Moacir Alves Borges; Fernando Cendes; Carlos Alberto Mantovani Guerreiro; Li Min Li (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To assess the epilepsy treatment gap in Campinas and São José do Rio Preto, two cities in the State of São Paulo, Brazil. METHOD: The treatment gap was estimated using the formula n1-n2/n1x100, where n1 was calculated using 1.86% prevalence and represented the number of individuals with epilepsy, while n2 represented the number of people who could be treated with an adult standard dose for a year utilizing the antiepileptic drugs supplied by the public health system. RESULTS: Our estimates revealed that in 2001, approximately 50% of the population with epilepsy was treated with the recommended antiepileptic medication. CONCLUSION: These results suggest that a relevant percentage of patients with epilepsy are not untreated. Further epidemiological studies are needed to investigate the reasons for this treatment gap so that interventions can reduce this gap and improve the quality of life of patients with epilepsy. OBJETIVO: Estimar a lacuna de tratamento em epilepsia nas cidades de Campinas e São José do Rio Preto, interior do Estado de São Paulo. MÉTODO: Estimamos a lacuna de tratamento através da fórmula n1-n2/n1x100, onde se utiliza o número de pessoas com epilepsia, calculado pela prevalência (n1), e a quantidade de pessoas que podem ser tratadas com a dose padrão para adultos das DAEs, distribuídas no período de um ano na localidade (n2). Usamos a prevalência estimada de 1,86% e consumo de medicação antiepiléptica fornecida pela rede básica de saúde nestas duas cidades. RESULTADOS: Nossas estimativas mostram que somente em torno de metade da população com epilepsia foi tratada em 2001 usando doses preconizadas de medicação antiepiléptica. CONCLUSÃO: A nossa estimativa aponta que uma parcela importante dos pacientes com epilepsia não está sendo tratada no nosso meio. Estudos epidemiológicos futuros devem explorar os motivos desta lacuna de tratamento para que intervenções sejam realizadas para melhorar a qualidade de vida dos pacientes com epilepsia.